Response of Soursop (Annona muricata L.) to Clonal Multiplication through Budding and Rootstock Compatibility - Sushma, M. S.; Rao, Venkata; Rajeshwari, R.; Swamy, G. S. K. (International Journal of Bio-resource and Stress Management, 2023)
A research trial was carried out at the College of Horticulture, Mysuru, University of Horticultural Sciences, Bagalkot, Karnataka, India during January–June 2021 to study the effect of different environmental conditions and rootstocks on success and survival of soursop budlings. There were 6 treatment combinations consisting of different rootstocks of Annona sp. (Annona muricata and Annona squamosa) along with growing conditions (polyhouse, 50% shade net and open condition) were replicated thrice in factorial completely randomized design. The results of the study indicated that soursop scion budded on its own rootstock (A. muricata) and placed under polyhouse condition had significantly affected on days taken to bud sprout (34.96 days), success (91.60%), survival percentage (85.30%) and growth parameters like number of leaves (3.81, 6.56 and 13.67), length of sprouted shoot (3.58 cm, 8.19 cm and 15.42 cm), girth of sprouted shoot (1.35 mm, 1.86 mm and 2.08 mm), number of nodes (3.52 , 6.11 and 11.67) and length of internode (1.20 cm, 1.47 cm and 1.73 cm) at 60, 90 and 120 days after budding whereas A. muricata scion budded on A. squamosa rootstock kept under open condition recorded more number of days for sprouting (37.86), least success (37.86%), survival percentage (85%) and growth parameters like number of leaves (2.33, 4.44 and 11.11), shoot length (2.78 cm, 5.51 cm and 11.13 cm), diameter of shoot (0.70 mm, 1.01 mm and 1.24 mm), number of nodes (2.11, 4.33 and 10.22) and node length (0.84 cm, 1.01 cm and 1.42 cm).